Ghaflah dan Counterterm-nya dalam Al-Qur’an Menurut Tafsir fi Ẓilal Al-Qur’an - Nur, Muhammmad Syawwaluddin; Isnaeni, Ahmad; Masruchin, Masruchin (Global Education Journal, 2024)
Al-Qur'an is a very important primary source because it includes everything that humans need. However, in reality, not everyone living in this world receives guidance in their lives. The aim of this research is to explore the concept of ghaflah (negligence) and identify terms or concepts that are opposed to it in the Al-Qur'an, using Sayyid Qutb's tafsir as an analytical framework. This research method uses library research, so the technique used for data processing consists of evaluating data obtained from data collection techniques then grouping and categorizing the data according to the problem being studied and then analyzing it. The results of the research show the meaning of ghaflah and its counterterms in the interpretation of Fi Dzilal al-Qur'an. First, ghaflah is negligent behavior that deliberately ignores all of God's gifts in the form of guidance, guidance, favors, gifts, and signs of His greatness, as well as indifference to oneself and one's surroundings. Second, the counterterms of ghaflah are gratitude and dhikr. Being grateful to Allah means being aware of the blessings Allah has given you and doing dhikr as an effort to remember that Allah is the strongest.